Repurposing Dimetridazole and Ribavirin to disarm Pseudomonas aeruginosa virulence by targeting the quorum sensing system - Yuan, Yang; Yang, Xiting; Zeng, Qianglin; Li, Heyue; Fu, Ruyi; Du, Lianming; Liu, Wei; Zhang, Yamei; Zhou, Xikun; Chu, Yiwen; Zhang, Xiuyue; Zhao, Kelei (Frontiers in Microbiology, 2022)
Pseudomonas aeruginosa relies on its complex cellular regulatory network to produce a series of virulence factors and to cause various acute and chronic infections in a wide range of hosts. Compared with traditional antibiotics which frequently accompany with widespread antibiotic resistance, crippling the virulence system of bacteria is expected to be a promising anti-infective strategy. In this study, Dimetridazole and Ribavirin, which had poor antibacterial activities on P. aeruginosa reference isolate PAO1 in nutrient medium but significantly inhibited the growth of P. aeruginosa PAO1 in M9-adenosine, were selected from 40 marketed compounds with similar core structure (furan, benzofuran, or flavonoids) to the acyl-homoserine lactone signals of P. aeruginosa quorum sensing (QS) system. The production of QS-controlled proteases, pyocyanin, and biofilm formation of P. aeruginosa PAO1 and the clinical isolates were significantly decreased by the presence of Dimetridazole or Ribavirin. Correspondingly, the majority of QS-activated genes in P. aeruginosa, including the key regulatory genes lasR, rhlR, and pqsR and their downstream genes, were significantly inhibited by Ribavirin or Dimetridazole, as determined by RNA-sequencing and quantitative PCR. Furthermore, the susceptibilities of drug-resistant P. aeruginosa isolates to polymyxin B, meropenem, and kanamycin were remarkably promoted by the synergistic application of Dimetridazole or Ribavirin. Finally, the treatment of Ribavirin or Dimetridazole effectively protected Caenorhabditis elegans and mice from P. aeruginosa infection. In conclusion, this study reports the antivirulence potentials of Dimetridazole and Ribavirin on P. aeruginosa and provides structural basis and methodological reference for the development of anti-pseudomonal drugs.